Managing the value of composts as organic amendments and fertilizers in sandy soils - Castán, Elisa (2016)
Nutrient rich composts are employed at low rates to minimize risks of N and P losses; this limits their value as soil improvers through C addition and the build up of soil organic matter. Blending with nutrientpoor composts such as those from the organic fraction of municipal solid waste could reduce the risks of nutrient losses while maintaining the positive effects on soil organic matter. We conducted a 2-yr experiment with composts of diverse origin: organic fraction of municipal solid waste (MC), cattle feedlot manure (FC), poultry litter (PC) and biosolids (BC), alone or blended (FC-MC, PC-MC) in a sandy soil under the humid warm climatic conditions of NE Argentina. We studied the effects of a single application (40 Mg ha 1) on the surface soil (0–10 cm) properties of a permanent subtropical pasture through annual chemical and biological analyses. On five dates, available N and P were also determined at 0–10 cm and 55–65 cm. Soil total C and N increased over time while potential N mineralization and CO2 emission decreased. All amendments resulted in similar increments of soil C and N despite marked differences in quantity and quality of organic matter inputs. Because MC had substantial amounts of Ca carbonates, it contributed to a reduction of available P from manure composts through dilution and precipitation. The release of available P from biosolids composts (where P is bound to Fe and Al) was lower than from manure composts (where P is bound by Ca phosphates). The highest environmental risk from compost application would likely be the leaching of soluble N produced during the composting process and released immediately after field application. Blending with N-poor MC would contribute to nitrate dilution.